Para onde sopram os ventos :politicas públicas de turismo no grande Pirambu/Fortaleza/CE - Santos, Maria Francineila Pinheiro dos (2006)
PARA ONDE SOPRAM OS VENTOS , metaphor used to indicate turism public politicsway to the west zone of Fortaleza, against the direction where until now this public politics was targeted, to the east zone. This context, análise the public politics implemented in the Grande Pirambu, so like the processes of nonterritorialization and reterritorialization unchain by the program os settlement and indemnification of the Projeto Costa Oeste. Aim to learn the transformations that unroll in the studied área, based in proceding methodologic that privileged the interviews with many social actors resettled, indemnificators, intirenants, livers and fishmen. The public politics analyzes run to the Grande Pirambu infer that the same answer at trying of urbam requalification of the área, object of the new exigence pretender by the touristics activities developed in Fortaleza, wish to incorporate this área at the turistics dynamic of the city. However, the implementation of the Projeto Costa Oeste do not occuring in calm way, by opposite sence the beginning, the same has been propitiated polemics and discussions, stired up about public politics between the municipa and state power, to bring about injury in the public coffers, to the developing turismo f the city and, mainly to the living around Grande Pirambu, unquiet and sad with the buildings of the referring project that there is running for four years